2002
DOI: 10.1051/0004-6361:20020883
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between expansion velocity and morphology in planetary nebulae

Abstract: Abstract. It is usually accepted that the differing morphological classes of planetary nebulae (PNe) arise from progenitors of differing mass. The primary evidence for this derives from the differing galactic distributions of the sources. This, if true, would be expected to result in other differences as well, including variations in the kinematics of the nebular envelopes. We point out here that there is now sufficient evidence to determine that this is the case. We find that BRET-type sources (i.e. nebulae p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Phillips & Mampaso 1988; Phillips & Ramos‐Larios 2008a). Similarly, observed gas outflow velocities are of the order of 18.2 ± 1.1 km s −1 – a value at the lower end of the planetary nebula range; spherical nebulae, for instance, have values V EXP ≅ 24.8 ± 1 km s −1 (Phillips 2002). The wings of the lines often show velocities extending up to ∼370 km s −1 , however (Corradi & Schwarz 1995).…”
Section: Introductionmentioning
confidence: 93%
“…Phillips & Mampaso 1988; Phillips & Ramos‐Larios 2008a). Similarly, observed gas outflow velocities are of the order of 18.2 ± 1.1 km s −1 – a value at the lower end of the planetary nebula range; spherical nebulae, for instance, have values V EXP ≅ 24.8 ± 1 km s −1 (Phillips 2002). The wings of the lines often show velocities extending up to ∼370 km s −1 , however (Corradi & Schwarz 1995).…”
Section: Introductionmentioning
confidence: 93%
“…It also appears that the diameters of the BPNe refer primarily to the bright cores of these sources, rather than the more extended nebular lobes. Phillips (2003b) has shown that such cores are probably similar in size to the envelopes of circular and elliptical PNe, given similar levels of surface brightness, and that their velocities of expansion are also comparable (Phillips 2002a). These various morphological types (i.e.…”
Section: Properties Of the Observed Zanstra Temperaturesmentioning
confidence: 99%
“…This is consistent with the mean trends in latitude cited above, and suggests that elliptical sources are associated with a large range of progenitor masses. Similarly, there appear to be small but significant variations in the velocities of expansion of the sources (Phillips 2002a), although their dimensions are similar where brightness temperatures are comparable (Phillips 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the evidence of shell expansion in Magellanic Cloud planetaries (Stanghellini et al 1999), and the invariance of observed expansion velocities V EXP with nebular radius (Phillips 2003d). Although there are systematic differences in velocity between the differing shell morphologies, these appear to be small (Phillips 2002a). Finally, we note that hydrodynamical models of expansion imply both acceleration and deceleration of the I-fronts (see e.g.…”
Section: The Expected Relation Between Brightness Temperature and Mormentioning
confidence: 72%